Inclusive Design and Textile Technology in the Everyday Lives of Wheelchair Dependent - Ferreira, Veridianna Cristina Teodoro; Carvalho, Agda [UNESP] (Springer Nature, 2018)
This paper discusses the benefits of textile technology to inclusive design, focusing on aspects that prioritize comfort and health for wheelchair dependent individuals. To this end, the focus of this paper is the ergonomics of products designed for the disabled, as well as their conception. It investigates the development of a form of technological processing based on applying microcapsules to textile materials, in addition to exploring its many functionalities and the possibilities for widening its scope of application, particularly relating to the contact of the fabric with the skin. The process reported here deals with people with mobility difficulties, specifically wheelchair dependents, having as its goal the prevention of pressure ulcers. To exemplify these possibilities, the research work carried out by designer Elisa Marangon Beretta is presented, wherein microcapsules of eicosane are applied onto polyurethane foam, used in wheelchair seats, with the purpose of contributing to the comfort and well-being of wheelchair dependents. New possibilities of textile processing are further explored, relating to the use of microencapsulation for offering greater comfort, preventing pressure ulcers and providing better adaptation approaches to increase the ability of physically disabled people to participate in everyday life, and hence improve their general health.
Keywords: Inclusive design; Microencapsulation; Textile technology; Wheelchair dependent